2010
DOI: 10.1016/j.jcmg.2009.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Comparison of Quantitative Volumetric Analysis of the Right Ventricle

Abstract: Volumetric quantification of RV volume was performed on CMR, CCT, and RT3DE images. Eliminating analysis-related intermodality differences allowed fair comparisons and highlighted the unique limitations of each modality. Understanding these differences promises to aid in the functional assessment of the RV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(131 citation statements)
references
References 22 publications
5
121
2
3
Order By: Relevance
“…7D). Recent studies have confirmed that 3DE measurements of the RVEF are accurate, reproducible, and correlate well with CMR both in adults and children [20,21,27,28]. In the most recent meta-analysis aimed at exploring the accuracy of different imaging modalities (2DE, 3DE, radionuclide ventriculography, computed tomography [CT], gated single-photon emission CT, and invasive cardiac cineventriculography) for RVEF using CMR as a reference method, 3DE has proven to be the most reliable technique, overestimating the RVEF by only 1.16% with the lowest limits of agreement (form -0.59 to 2.92%) [29].…”
Section: Right Ventricular Function Right Ventricular Systolic Functionmentioning
confidence: 80%
See 1 more Smart Citation
“…7D). Recent studies have confirmed that 3DE measurements of the RVEF are accurate, reproducible, and correlate well with CMR both in adults and children [20,21,27,28]. In the most recent meta-analysis aimed at exploring the accuracy of different imaging modalities (2DE, 3DE, radionuclide ventriculography, computed tomography [CT], gated single-photon emission CT, and invasive cardiac cineventriculography) for RVEF using CMR as a reference method, 3DE has proven to be the most reliable technique, overestimating the RVEF by only 1.16% with the lowest limits of agreement (form -0.59 to 2.92%) [29].…”
Section: Right Ventricular Function Right Ventricular Systolic Functionmentioning
confidence: 80%
“…The RVEF is an independent predictor of cardiovascular morbidity and mortality in various conditions [2,27]. The assessment of RVEF using 2DE is no longer recommended due to its inaccuracy [9,12].…”
Section: Right Ventricular Function Right Ventricular Systolic Functionmentioning
confidence: 99%
“…Three-dimensional of the RV has been validated against CMR in various cardiovascular diseases [34,35]. It can be a key player in patients after cardiac surgery, when traditional longitudinal parameters (e.g.…”
Section: Wwwcardiologyjournalorgmentioning
confidence: 99%
“…Assessment of RV volume and ejection fraction by MDCT has been shown to correlate well with CMR (Table 1). [14][15][16][17] It is important to note that the evaluation of RV by MDCT can be limited by inadequate contrast opacification, resulting in problems with accurate delineation of RV contours. It has been reported that RV cannot be accurately assessed by MDCT in as many as 5 to 17% of studies.18 When accurate delineation of RV contours is necessary, biphasic or triphasic contrast protocols with a saline and contrast chaser mixture can be used.…”
Section: Right Ventricle (Evaluation Of Volume and Function)mentioning
confidence: 99%